An Assessment of Soil/Land Erosion: Management and Conservation - Dr. Sanjay Shahi (International Journal of Engineering and Management Research, 2019)
Land degradation is an environmental threat to all natural ecosystems in India, including agricultural, forest, pasture, and human sustainability. It has severe impacts on agricultural and soil productivity, aquatic imbalance, damaged drainage networks, deterioration of water quality in rivers and reservoirs, infrastructure, and the environment. The soil structure, water systems, natural habitats, and ecosystem services are all adversely affected. Land degradations exacerbated by factors such as an expanding population, intensive agriculture, deforestation, overgrazing, and an increase in the need for wood for heating. Sheet and rill erosion are the primary causes of soil loss due to water erosion. Soil is a dynamic mixture of minerals and organic matter that either supports plant growth or has the ability to do so. Because of the complex interactions among parent material, climate, biology, slope, and time, soil formation is often considered a long-term endeavor in geology. The most important resource on Earth is soil, which serves as the foundation for life. The depletion and degradation of a fertile productive base are both consequences of soil erosion, which takes place at a much slower pace. Sustainable development can only be achieved through proper soil conservation and management. Identifying and describing the factors contributing to Land degradation in India is the focus of this research, which also seeks to demonstrate the severity of the problem. Third, to discuss the implications of Land degradation and actions taken in India to combat the problem of soil erosion.